2000
DOI: 10.1152/ajpheart.2000.278.5.h1500
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of cardiac ANP and BNP mRNA in different stages of experimental heart failure

Abstract: Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) are cardiac hormones that are involved in water and electrolyte homeostasis in heart failure. Although both hormones exert almost identical biological actions, the differential regulation of cardiac ANP and BNP mRNA in compensated and overt heart failure is not known. To study the hypothesis that cardiac BNP is more specifically induced in overt heart failure, a large aortocaval shunt of 30 days duration was produced in rats and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 43 publications
(48 reference statements)
5
69
1
Order By: Relevance
“…Our data indicate that changes occur in the expression of these genes, and that these changes are coincident with the onset and progression of the structural and metabolic changes seen in the db/db group. The recapitulation of the fetal gene program (i.e., an MHC isoform switch from predominantly ␣ to ␤, decreased SERCA2a, and increased ANP) classically occurs to varying extents in response to a number of mechanical insults, including thoracic aortic constriction (15,34), pacing-induced heart failure (52), and aortocaval shunting (37). However, there is a growing body of evidence that certain metabolic disturbances, including hypothyroidism (24), dexamethasone treatment (21), gonadectomy (57), and a high-cholesterol diet (32), produce these changes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that changes occur in the expression of these genes, and that these changes are coincident with the onset and progression of the structural and metabolic changes seen in the db/db group. The recapitulation of the fetal gene program (i.e., an MHC isoform switch from predominantly ␣ to ␤, decreased SERCA2a, and increased ANP) classically occurs to varying extents in response to a number of mechanical insults, including thoracic aortic constriction (15,34), pacing-induced heart failure (52), and aortocaval shunting (37). However, there is a growing body of evidence that certain metabolic disturbances, including hypothyroidism (24), dexamethasone treatment (21), gonadectomy (57), and a high-cholesterol diet (32), produce these changes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggest that ANP and BNP share a common regulatory mechanism and that their synthesis may be commonly associated with atrial stretch. Indeed, wall stretch is known to be an important factor in the induction of ANP and BNP genes in cardiac tissue in CHF (Yasue et al 1994;Magga et al 1997, Langenickel et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…BNP is considered to be a more reliable prognostic marker than ANP in patients with CHF (Friedl et al 1999), and BNP levels found in the atrium are proportionally related to the severity of the disease (Mukoyama et al 1991;Langenickel et al 2000). Doyama et al (1998) observed that BNP levels rise in response to increased atrial pressure and that atrial expression of BNP mRNA is correlated with that of ANP, assuming that these two genes may share some common regulatory mechanism, of which atrial pressure was suggested to be of major importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, shunt closure has been reported in 7% of the cases, which means that it is necessary to confirm the patency of the shunt at the end of investigation. Of note that, not only the duration, but also the size of the shunt will determine the onset and severity of CHF in rats, with elevation of LV end-diastolic pressure reported only in the overt CHF group caused by a large shunt for a minimum period of 4 weeks [148]. This procedure has the advantage of being fast and usually well tolerated, despite the limitation of requiring a laparotomy.…”
Section: Volume-overload-induced Hfmentioning
confidence: 99%